2004
DOI: 10.1080/0268051042000280138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of web-logs (blogs) on student perceptions of isolation and alienation in a web-based distance-learning environment

Abstract: In the rush to promote the use of computer-mediated technologies for both traditional and distance learning, relatively little research has been conducted about learner feelings of isolation, alienation and frustration. More recent technologies such as web-logs (blogs) may provide a wider range of tools for bridging learners' feelings of isolation. The purpose of this research is to investigate the impact of using blogs in a web-based learning environment. This qualitative investigation presents an interpretiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(120 citation statements)
references
References 9 publications
3
112
0
5
Order By: Relevance
“…This includes use of blogs as a means by which the isolation of pre-service trainee teachers can be alleviated through communication with peers (Dickey 2004). This also links with previous research done by the author Hramiak in this field, looking at the use of VLEs to reduce the isolation and loneliness felt by trainee teachers on placement (Hramiak 2007).…”
Section: Introductionmentioning
confidence: 56%
“…This includes use of blogs as a means by which the isolation of pre-service trainee teachers can be alleviated through communication with peers (Dickey 2004). This also links with previous research done by the author Hramiak in this field, looking at the use of VLEs to reduce the isolation and loneliness felt by trainee teachers on placement (Hramiak 2007).…”
Section: Introductionmentioning
confidence: 56%
“…The research culture of higher education also means that it is more likely than in the school sector that published material will go beyond mere description to provide evidence for claims. Articles promoting the use of blogging in higher education (Downes, 2004) and reporting the results of early research (Dickey, 2004;Williams & Jacobs, 2004) were already appearing as the concept of Web 2.0 began to emerge (O'Reilly, 2005).…”
Section: Web 20 In Higher Educationmentioning
confidence: 99%
“…I selected this methodology because other researchers doing similar studies of blogs and bloggers and similar short texts have found it to be a useful way to approach such a collection of material (Bishop, 2010;Dickey, 2004;Guzzetti & Gamboa, 2005;Kerawalla, Minocha, Kirkup, & Conole, 2009;Luehmann, 2008;Park, Heo, & Lee, 2011;Purcell-Gates, Perry, & Briseño, 2011). I accessed each blog post via its corresponding link reference on the meta-blog mentioned above.…”
Section: Data Collection and Analysismentioning
confidence: 99%